A fixed-frequency hysteretic buck converter with novel adaptive window control and transient response improvement - Jia, Meng (2021)
This study presents a fixed-frequency hysteretic buck converter designed and fabricated using 0.18-µm complementary metal–oxide–semiconductor process. With a phase-locked loop (PLL)-based adaptive window control, the proposed buck converter can achieve a fixed switching frequency, and this frequency can be tuned within a certain range through a reference clock frequency. Concurrently, a novel auxiliary circuit is proposed to monitor the converter's output loading dynamics to reduce the converter's transient recovery time. It will also help to regulate the output voltage at the steady-state operation as well. With the supply voltage ranging from 3 to 4.2 V and an output voltage of 1.8 V, the simulated switching frequency is maintained at 10 MHz because of the PLL control. The transient response time is only 0.3 and 0.4 µs for a 400 mA step-up load and step-down load, respectively.